(untitled) (Research, Society and Development, 2021)
This study aims to analyze the school feeding transition process by taking into account the changes in the structure of its production space. An ethnographic research was carried out in a public school located in a low-income neighborhood in the city of Salvador (Bahia, Brazil) from October to December 2014 by mainly interviewing the school lunch handlers in that institution. In order to establish a dialogue with the empirical data gathered in the field, scientific publications and official documents were analyzed. Results show the transition from the “Cafeteria” to the “Nutrition and Food Unit” was shown to prevail much more at the conceptual than at the structural level, thus producing two symbolic spaces: the “ideal kitchen”, fully in line with both the legislation and the content regarding the handlers’ training, and the “real kitchen”, in which everyday practices take place. Further advances in PNAE-related policies should consider listening to all personnel involved in the process and undertake a critical reflection about their effectiveness in school settings.